Colonial Search for a Southern Eden. - Wright, Louis B. (University of Alabama Press, 1953)
European imperialists began to dream of other kinds of wealth besides gold in the New World Louis Booker Wright was a graduate of Wofford College, and was at various times a John Simon Guggenheim Fellow and a Benjamin Franklin Medalist, and he held honorary degrees from, among others, Princeton, Tulane, and California State University-Fulerton. He was the author of a number of books, including The Atlantic Frontier: Colonial American Civilization 1607-1763, Gold, Glory, and the Gospel: the Adventurous Lives of the Renaissance Explorers, Culture on the Mov.